1966
DOI: 10.1901/jeab.1966.9-443
|View full text |Cite
|
Sign up to set email alerts
|

PROBABILISTICALLY REINFORCED CHOICE BEHAVIOR IN PIGEONS1

Abstract: A single principle, "momentary maximizing", may account for much of a pigeon's steadystate behavior in both probability learning and concurrent variable interval experiments. The principle states that a pigeon tends to choose the alternative that momentarily has the higher probability of reinforcement. A successive discrimination procedure, which produced matching in an earlier experiment, produced here a tendency to maximize if training were adequately extended. Maximizing was produced also by other procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
275
2
3

Year Published

1972
1972
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 263 publications
(300 citation statements)
references
References 13 publications
(19 reference statements)
19
275
2
3
Order By: Relevance
“…In the present case, for instance, careful reading of the basic literature reveals that debate is unresolved about whether or when ratio-like schedules contribute to matching (Green, Rachlin, & Hanson, 1983;Herrnstein & Heyman, 1979;MacDonnall, 1988;Savastano & Fantino, 1994;Shimp, 1966;Shurtleff & Silberberg, 1990). Gaps in basic research limit the functional parallels that can be drawn when a laboratoryderived equation is fit to field data.…”
Section: Applying Quantitative Models To Field Observations: Special mentioning
confidence: 79%
“…In the present case, for instance, careful reading of the basic literature reveals that debate is unresolved about whether or when ratio-like schedules contribute to matching (Green, Rachlin, & Hanson, 1983;Herrnstein & Heyman, 1979;MacDonnall, 1988;Savastano & Fantino, 1994;Shimp, 1966;Shurtleff & Silberberg, 1990). Gaps in basic research limit the functional parallels that can be drawn when a laboratoryderived equation is fit to field data.…”
Section: Applying Quantitative Models To Field Observations: Special mentioning
confidence: 79%
“…The fact that information theory provides an elegant description of how pigeons track rapidly changing statistical information in the serial reaction time task may clarify a possible mechanism underlying the molecular position, according to which pigeons generally can and do track continuous changes in reinforcement probability and may even do so with nearly optimal precision. Such a position is called momentary maximizing (Hinson & Staddon, 1983;Shimp, 1966Shimp, , 2004. In particular, if local reinforcement probability is viewed as local uncertainty, then processing local reinforcement probability is processing local statistical information.…”
Section: Processing Of Statistical Information and Molecular And Molamentioning
confidence: 99%
“…Following reinforcement, the initial links were reinstated. If both terminal Shimp (1966) has shown that pigeons' choices of an alternative often vary as a function of the location of previous responses (left or right). The present study examined choice as a function of the time since the last choice response (interresponse time or IRT).…”
Section: Choice Proportions For Terminal-linkmentioning
confidence: 99%